Optimising community pharmacy intervention in managing sleep disorders: extended roles of community pharmacists - Mohamad Noor, Zaswiza; Smith, Alesha J.; Smith, Simon S.; Nissen, Lisa M. (Malaysian Pharmaceutical Society, 2015)
Community Pharmacists are in a position to provide advice and services of sleep-related disorders to the community. Interventions that measure sleep/wake objectively can assist pharmacist in consultation. This feasibility study was conducted to evaluate: (1) the effectiveness of a ‘community-pharmacy-based’ intervention, (2) the role of actigraph and (3) the extended role of community pharmacist, in managing sleep disorders. Customers with sleeping disorders were recruited based on convenience sampling. The intervention-care-group (ICG) (n=20) received an ‘intervention-package’ including: a wrist-worn actigraph (to measure sleep/wake patterns for 2-weeks), a sleep-diary and two consultations. Actigraphy sleep-parameters (sleep efficiency%, SE%; total-sleep-time, TST; sleep-onset-latency, SOL) were downloaded at week-1 (pre) and week-2 (post) for consultation used. The usual-care-group (UCG) (n=21) received ‘standard-care’ for sleeping disorders. Both groups completed sleep-scale scores (Epworth Sleepiness Scale, ESS; Insomnia Severity Index, ISI) at baseline (pre) and the end-of-study (post). All subjects answered Likert-type-scale questionnaires to determine their understanding of sleep disorders after week-2. Findings showed significant differences (p<0.05) when comparing pre- and post-ISI mean scores in ICG and post-ISI mean scores between ICG and UCG. For SE%, an increase of subjects rated as ‘good sleepers’ at post–assessment in ICG was observed. Actigraphy sleep-parameters mean scores showed agreement with the sleep-diary. ICG showed 35% of subjects agreed to have improve understanding of sleep disorders after consulting the pharmacist, compared to UCG (4.8%). ISI scores offer insights into development of a community-pharmacy-based intervention, particularly in individuals with insomnia symptoms. It also demonstrated that actigraph could provide objective sleep/wake data to assist community pharmacists during consultations on sleep health.